Pharmacognostic Standardization and Phytochemical Evaluation of Ailanthus altissima (Mill.) Swingle leaves - Bashir, Andleeb; Mohi-ud-din, Roohi; Farooq, Saeema; Bhat, Zulfiqar Ali (Journal of Drug Delivery and Therapeutics, 2019)
The present study was focussed to carry out the detailed pharmacognostic studies in terms of organoleptic characters, physicochemical parameters, macroscopical, microscopical characters and phytochemical screening for major groups of compounds and other WHO recommended parameters for standardization of the leaves of (Mill.) family Simaroubaceae. Phytochemical screening of methanolic and aqueous extracts of leaves of Ailanthus altissima demonstrated the presence of Carbohydrates, flavonoids, tannins, cardiac glycosides, phenols, saponins, diterpenes, fats and oils. However alkaloids and anthraquinone glycosides were found absent in all the extracts. Information obtained from phytochemical and pharmacognostical analysis can be used as markers in the identification and standardization of this plant for monograph development and as herbal remedy. Keywords: Tree of heaven, Phytochemical, Pharmacognostic analysis, Bioactive compounds, Ailanthus altissima.